Climate Change Reveals Contractions and Expansions in the Distribution of Suitable Habitats for the Neglected Crop Wild Relatives of the Genus Vigna (Savi) in Benin - Manda, Leonard; Idohou, Rodrigue; Assogbadjo, Achille Ephrem; Agbangla, Clement (Frontiers in Conservation Science, 2022)
Sustainable conservation of crop wild relatives is one of the pathways to securing global food security amid climate change threats to biodiversity. However, their conservation is partly limited by spatio-temporal distribution knowledge gaps mostly because they are not morphologically charismatic species to attract conservation attention. Therefore, to contribute to the conservation planning of crop wild relatives, this study assessed the present-day distribution and predicted the potential effect of climate change on the distribution of 15 Vigna crop wild relative taxa in Benin under two future climate change scenarios (RCP 4.5 and RCP 8.5) at the 2055-time horizon. MaxEnt model, species occurrence records, and a combination of climate- and soil-related variables were used. The model performed well (AUC, mean = 0.957; TSS, mean = 0.774). The model showed that (i) precipitation of the driest quarter and isothermality were the dominant environmental variables influencing the distribution of the 15 wild Vigna species in Benin; (ii) about half of the total land area of Benin was potentially a suitable habitat of the studied species under the present climate; (iii) nearly one-third of the species may shift their potentially suitable habitat ranges northwards and about half of the species may lose their suitable habitats by 5 to 40% by 2055 due to climate change; and (iv) the existing protected area network in Benin was ineffective in conserving wild Vigna under the current or future climatic conditions, as it covered only about 10% of the total potentially suitable habitat of the studied species. The study concludes that climate change will have both negative and positive effects on the habitat suitability distribution of Vigna crop wild relatives in Benin such that the use of the existing protected areas alone may not be the only best option to conserve the wild Vigna diversity. Integrating multiple in situ and ex situ conservation approaches taking into account “other effective area-based conservation measures” is recommended. This study provides a crucial step towards the development of sustainable conservation strategies for Vigna crop wild relatives in Benin and West Africa.